Low grade thermal energy driven-small scale absorption refrigeration system (SSARS): Design, fabrication and cost estimation. (March 2022) - Modi, Bhaumik; Mudgal, Anurag; Raja, Bansi D.; Patel, Vivek
Graphical abstract: Highlights: Cooling by using solar thermal or any other open heat source as input energy. Absorber uses a vertical tube heat exchanger. Evaporator is a double pass flooded heat exchanger. Break-even point of 4.5 years is determined. Recommended design reduces greenhouse gases emission by about 77%. Abstract: Design methodology of small-scale single effect LiBr (Lithium bromide)/water absorption refrigeration system with a capacity of 1.5 Ton is prepared and tested. The system delivers cooling by using solar thermal or any low-grade thermal energy. A double-helical coil heat exchanger works as a condenser and solution heat exchanger. Helically coiled heat exchangers have a better compactness and heat transfer co-efficient so that condenser and solution heat exchanger are designed in similar way for a rated capacity. In the design, evaporator is a double pass flooded heat exchanger, the cross-section of the evaporator is set based on the hydrostatic pressure effect. In experiments, the generator temperature of the proposed unit varied in the range of 80 to 100˚C and results indicate that the maximum system COP of 0.35 at the generator temperature of 92˚C. Simultaneously, the cooling load of the system increased from 4.6 kW to 5.16 kW by raising the evaporator temperature from 8 to 15 ˚C. Break-even point of 4.5 years is determined for a small-scale absorption refrigeration system. This fact leads to possibilities of the wide use of small-scale absorption refrigeration systems as an economically viable option.